Language Contacts and Discourses in the Far North - Frick, Maria; Räisänen, Tiina; Ylikoski, Jussi (Arctic Encounters, 2023)
This open access book sheds light on 21st-Century multilingualism in the Far North of Europe - Finland, Sweden, Norway, and Estonia - an area with multifaceted contacts between many Uralic and Indo-European languages. These contacts are taking new forms as migration and English as the lingua franca are changing the linguistic situation remarkably. The national languages dominate the life of most inhabitants, while the use of indigenous Saami languages, old minority languages, and the languages of new immigrants is limited to certain areas or domains. This volume takes a close look at multilingual individuals and discusses how their lives are affected by different languages.